The Anticoagulation Dilemma: Concurrent Traumatic Brain Hemorrhage and Cerebral Venous Thrombosis in a Blast Injury Patient - Ayenew Amare; Mikiyas G. Teferi; Laltu M. Negasa; Tesfaye A. Haile; Selamawit M. Bonsu; Kalkidan P. Ageze; Gedefaw T. Minwagaw (Clinical Case Reports, 2026)
ABSTRACT Blast injuries produce complex multi‐system trauma through primary barotrauma, secondary penetrating projectiles, tertiary displacement forces, and quaternary mechanisms. Among the most challenging complications is the concurrent presentation of traumatic intracranial hemorrhage and cerebral venous sinus thrombosis (CVST), which creates a profound therapeutic dilemma regarding anticoagulation management. We present a 26‐year‐old male who sustained injuries from a high‐order explosive device that resulted in 19 fatalities. He presented 16 h post‐injury with a Glasgow Coma Scale score of 10/15 and marked quadriparesis with muscle power of 2/5 in all four limbs. Advanced neuroimaging ruled out cervical spine injury as the etiology of his motor deficits. Non‐contrast brain CT revealed a left posterior parietal comminuted and depressed skull fracture with multiple intracerebral bone fragments, associated hemorrhagic contusion, and perilesional edema. CT venography demonstrated extensive thrombosis of the superior sagittal sinus extending to the confluence of sinuses. Chest CT confirmed pulmonary contusions and subcutaneous emphysema. The patient received mannitol for cerebral edema management, phenytoin for seizure prophylaxis, and broad‐spectrum antibiotics. Following multidisciplinary consultation, therapeutic anticoagulation was withheld in the acute phase due to substantial risk of hemorrhage expansion from the adjacent contusion and penetrating bone fragments. The patient's neurological status stabilized over five days, though quadriparesis persisted at discharge. He was referred for neurosurgical evaluation and intensive rehabilitation, with anticoagulation initiated one week later. This case underscores that blast‐related TBI can produce severe central motor deficits without spinal injury, and that the coexistence of hemorrhagic contusion and CVST often contraindicates early anticoagulation, requiring individualized risk–benefit assessment and multidisciplinary decision‐making in severe neurotrauma.